Effects of exercise on the markers of iron status in serum of cross-country skiers - Malczewska-Lenczowska, J.; Stupnicki, R.; Gabrys, T. (Biology of Sport, 2010)
The study aim was to assess the within-subject, day-to-day variability for ferritin and soluble transferrin receptor (sTfR) concentrations in serum of 6 female and 8 male cross-country skiers aged 16-18 years under a regular training regimen throughout 8 consecutive days. The concentrations of iron status variables and creatine kinase (CK) activities were adjusted to plasma volume changes. Mean ferritin concentrations were 30.6 • 1.142±1 and 22.6 • 1.167±1 mikro-g/l for men and women, respectively, the average within-subject, mean day-to-day variability coefficients (CV) being 13.4% in men and 15.2% in women. Mean sTfR was 2.14 • 1.050±1 and 2.62 • 1.047±1 mg/l, respectively, and mean day-to-day CV 6.5% and 4.6%. Mean CV for sTfR/logFerr were 6.0% and 7.4%, respectively. Neither index correlated with training loads or CK activities. Thus, the training performed once daily had no significant effect on ferritin concentrations on the following morning, so ferritin alone may prove insufficient in detecting iron deficiency in endurance athletes. The low variability of sTfR under endurance loads made it useful in detecting iron deficiency together with ferritin and the sTfR/logFerr index. Adjusting the concentrations of ferritin and sTfR by changes in plasma volume might be recommendable for endurance athletes.